DIALEK-DIALEK BAHASA ARAB - Suaidi Suaidi (Adabiyyāt: Jurnal Bahasa dan Sastra, 2008)
In various Arabic literary works, especially the ones, which concern with Qoranic studies, it is argued that the Koran was recited in the dialect of Quraisy. All dialects of the Arabic language were renowned for their eloquence but the dialect of Quraisy was considered the most expressive and articulate, and thus over generations, it came to be known as the dialect of the Koran. Generally the dialects of classical Arabic can be classified into Hijaz, Syria, Iraq, Egypt, and Morocco. The variations on dialects are because of the following factors: first are the extrinsic factors, which consist of social, cultural, geographical, and political factors. Second are the intrinsic factors, which cover phonological, morphological, and syntactical factor. All of those factors have gone in the process of ibdāl, i’rab, binâ’, tashīh, ‘ilāl, itmām, naqs , etc.